Ruling elites rotation and asset ownership: Implications for property rights - Leonid Polishchuk; Georgiy Syunyaevy (Institut für Ost- und Südosteuropaforschung (IOS), 2014)
We provide a theory and empirical evidence indicating that the rotation of ruling elites in conjunction with elites asset ownership could improve property rights protection in non-democracies. The mechanism that upholds property rights is based on elites concern about the security of their own asset ownership in the event they lose power. Such incentives provide a solution to the credible commitment problem in maintaining secure property rights when institutional restrictions on expropriation are weak or absent.
urn:nbn:de:101:1-2014101419574
Keywords: K11; O17; P14; 330; endogenous property rights; credible commitment; “stationary bandit”